Role of tumour microenvironment in the development of lymphovascular invasion in breast cancer - Lakshmi Narasimha, Pavan (2020)
Lymphovascular invasion (LVI) refers to tumour cells invasion through the lymphatic space, blood vessel. Although the LVI mechanism has not been clearly demonstrated, LVI may reflect a surrounding tumour microenvironment that predicts aggressive tumour underlying thus worse prognosis. Therefore, intreaction of LVI with Tumour micro-environment (TME) is stressed in this particular study. TME comprises cellular components and non-cellular components like blood vessels and extra cellular matrix (ECM) surrounding a tumour. There is little evidence regarding the relation between LVI and TME. Epithelial–mesenchymal transition (EMT) plays a key role in the progression and metastasis of Breast cancer (BC). This research aimed to explore the clinicopathological importance of Lipocalin 2 (LCN2), Solute carrier Family 22 member 17 (SLC22A17), Cluster of Differentiation-276 (CD276 or B7-H3) and Leukocyte associated immunoglobulin like receptor-1 (LAIR-1) in BC cohort. LCN2 plays a major role in the BC transition from EMT, angiogenesis, cell migration, and invasion. Notably, LCN2 functions by involving multiple signalling pathways as an initiator of carcinogenesis and metastasis. The exact mechanism between LCN2 and SLC22A17 is not completely understood. CD276 is an important member of the B7 family of immune checkpoints expressed on antigen presenting cells and plays an important role in inhibiting the activity of T cells. Importantly, on a broad range of human solid tumours, CD276 is over-expressed and often associated with both adverse prognosis and bad clinical results in patients. LAIR-1 is an inhibitory receptor that is expressed on many leukocytes and on most types of hematopoietic cells and negatively regulate immune response, but the role of LAIR-1 in tumor micro-environment and its possible mechanism of action in LVI is clearly not understood. Thus, in the current study we evaluated each marker using a well characterized breast cancer cohort to evaluate the impact on TME.